2020
DOI: 10.1111/jcmm.16052
|View full text |Cite
|
Sign up to set email alerts
|

Elabela may regulate SIRT3‐mediated inhibition of oxidative stress through Foxo3a deacetylation preventing diabetic‐induced myocardial injury

Abstract: Diabetes, a metabolic disease characterized by hyperglycaemia, is known to be caused by insulin resistance and insulin secretion dysfunction. In recent years, diabetes mellitus has become an epidemic and now represents one of the most prevalent disorders. The major cause of mortality and morbidity in diabetic patients is due to cardiovascular complications. 1 Diabetic cardiomyopathy (DCM) is characterized, in its early stages, by diastolic relaxation abnormalities and, in later stages by clinical heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Diabetes mellitus, a metabolic disease characterized by chronic hyperglycemia resulting from insulin deficiency, is currently one of the most prevalent chronic medical conditions. Diabetes mellitus has been recognized as a major cardiovascular risk factor as it increases both cardiovascular morbidity and mortality ( Dia et al, 2020 ; Li et al, 2021 ). According to the American Diabetes Association, chronic hyperglycemia can cause long-term damage, dysfunction, and failure in various organs, including the eyes, kidneys, nerves, heart, and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus, a metabolic disease characterized by chronic hyperglycemia resulting from insulin deficiency, is currently one of the most prevalent chronic medical conditions. Diabetes mellitus has been recognized as a major cardiovascular risk factor as it increases both cardiovascular morbidity and mortality ( Dia et al, 2020 ; Li et al, 2021 ). According to the American Diabetes Association, chronic hyperglycemia can cause long-term damage, dysfunction, and failure in various organs, including the eyes, kidneys, nerves, heart, and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that concentrations of 4-hydroxynonenal and malondialdehyde are high in the hearts of 8-week-old SIRT3 −/− mice, and that 4 weeks of antioxidant treatment normalizes the 4-hydroxynonenal concentration ( 81 ). In another study, the expression of MnSOD and catalase were found to be high in the hearts of SIRT3 overexpressing mice ( 84 ), while a third study showed that elabela (a novel peptide that has effects via the apelin receptor) may induce the inhibition of OS by SIRT3 through the deacetylation of FOXO3a, thereby preventing myocardial injury in diabetes ( 85 ). Taken together, these findings imply that SIRT3 inhibits OS in DCM.…”
Section: Oxidative Stress- Related Pathwaysmentioning
confidence: 99%
“…Icariin has a cardioprotective effect in high-glucose-treated cardiomyocytes via upregulating apelin and SIRT3 expression, which can reverse diabetes-induced mitochondrial dysfunction; however, it did not affect the activity of SIRT3 in apelin silence samples ( 54 ). In addition, our previous research showed that Elabela can regulate the SIRT3-mediated inhibition of oxidative stress through Foxo3a deacetylation and prevent diabetic-induced myocardial injury ( 55 ). These results suggest that the apelin/SIRT3 signal pathway may be used as a novel therapeutic strategy for diabetes-related cardiovascular diseases.…”
Section: Effect Of Apelin–apj System On Diabetesmentioning
confidence: 99%